KREATIVITAS GURU DALAM PEMBELAJARAN DI MASA PANDEMI - Nur cahya Chahyani (UNIVERSITAS PGRI MADIUN, 2022)
AbstractCurrently the world is busy talking about the Corona Virus outbreak. The existence of the covid-19 virus in Indonesia currently has an impact on the entire community, where all outdoor activities are limited, people are prohibited from approaching crowds, social distancing (Social Distancing) and maintaining physical distance, the aim is to prevent the wider spread of COVID-19. Teacher creativity during a pandemic requires technological adaptation. Technology provides convenience in delivering information or learning materials so that learning activities do not become a special obstacle when learning online. This study aims to determine how creative teachers are in kindergarten. Barunawati II West Jakarta in the learning process is expected to be achieved properly where there is a creativity teacher who uses learning media, whatsapp applications, zoom, learning videos, home visits, limited face-to-face, utilizing technological sophistication that attracts students' attention which makes abstract concepts more interesting. concrete and easy to understand.Keywords: teacher creativity, study pandemic period AbstrakSaat ini dunia sedang ramai memperbincangkan mengenai wabah Virus Corona. Adanya virus covid-19 di Indonesia saat ini berdampak bagi seluruh masyarakat, dimana segala kegiatan diluar ruangan dibatasi, masyarakat dilarang mendekati keramaian, pembatasan sosial (Sosial Distancing) dan menjaga jarak fisik, tujuannya agar tidak terjadi penyebaran covid-19 lebih luas lagi. Kreativitas guru di masa pandemi memerlukan adaptasi teknologi. Teknologi memberikan kemudahan dalam penyampaian informasi atau materi belajar sehingga kegiatan pembelajaran tidak menjadi kendala khusus pada saat pembelajaran dalam jaringan.Penelitian ini bertujuan untuk mengetahui bagaimana kreativitas guru di TK. Barunawati II Jakarta Barat dalam proses pembelajaran diharapkan dapat tercapai dengan baik di mana benar adanya guru kreativitas yang menggunakan media pembelajaran aplikasi whathsapp, zoom, vidio pembelajaran, home visit, tatap muka terbatas, memanfaatkan kecanggihan teknologi yang menarik perhatian siswa yang menjadikan konsep abstrak menjadi lebih konkrit dan mudah dipahami.Kata kunci: kreativitas guru, pembelajaran masa pandemi